Exploring the effects of zolpidem on cognitive impairment and cellular changes using a lithium-pilocarpine rat model - Ahmed, Iman Imtiyaz (2021)
Post traumatic epilepsy occurs when seizures persist for > 1 week following a traumatic brain injury. The temporal lobe that houses the hippocampal formation is a common site for seizure initiation in these patients, resulting in cognitive and memory deficits. More than 30% of patients with post traumatic epilepsy are resistant to conventional anti-epileptic drugs such as diazepam, prompting the need to find new therapeutic options. There is also a lack of clinically translatable disease models of post traumatic epilepsy due to high animal mortality rates and low status epilepticus induction rates, making it difficult to test potential therapeutics. Therefore, in our study we utilized a new lithium-pilocarpine status epilepticus induction protocol that spanned a period of 4 days and comprised of fractionated doses of pilocarpine. Status epilepticus was graded using the Racine scale, completion of which was followed by the application of a suitable drug cocktail (diazepam- or zolpidem-cocktail) designed to reduce mortality rates. We also tested the effects of zolpidem on cognitive function in these animals using Morris water maze, while also utilizing Haematoxylin and Eosin staining to investigate morphological changes in the hippocampal formation following post traumatic epilepsy before and after zolpidem application. Our results showed a 100% status epilepticus induction rate with the 4-day induction protocol. We also observed a 0% mortality rate with the diazepam-cocktail which was successfully able to stop status epilepticus in the animals compared to the zolpidem-cocktail. The recovery time for animals treated with the diazepam-cocktail was also relatively shorter as compared to that of the zolpidem-cocktail, compelling us to proceed with diazepam-cocktail treated animals for further tests. Our behavioural test revealed that while most animals displayed exploratory behaviour, animals with post traumatic epilepsy that were administered zolpidem 30 minutes prior to the test exhibited thigmotaxic swimming pattern in the Morris water maze, a phenomenon common in models of fear and anxiety, suggesting zolpidem having a paradoxical anti-anxiolytic effect. Histological analysis of animals with post traumatic epilepsy showed a significant amount of cell loss and damage to the layers of the CA1, CA3, upper dentate gyrus, and subiculum. Comparatively, analysis of brain images from animals that were previously administered zolpidem during behavioural testing revealed an improvement in both the cell count and thickness of cell layers in the CA1, CA3, upper dentate gyrus, and subiculum regions, suggesting zolpidem to have a potential restorative effect.